2008
DOI: 10.1093/schbul/sbn085
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Processing in Persons at Risk for Schizophrenia

Abstract: Evidence suggests that individuals with schizophrenia demonstrate emotion-processing deficits. However, the nature and extent of emotion abnormalities in individuals considered at risk for schizophrenia have not been previously summarized. This article provides a review of the recent literature pertaining to emotion processing in 3 at-risk populations: those at familial high risk, those with schizotypal characteristics, and those in the putative prodrome to psychosis. Studies are reviewed across the components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
126
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 102 publications
9
126
2
2
Order By: Relevance
“…Although this study does not directly address cellular and molecular mechanisms of this phenomenon, one possibility is that it could result from a failure of higher cortical processes to limit the impact of stressors. The prefrontal cortex is a region that has been linked to the pathophysiology of schizophrenia (Knable and Weinberger, 1997;Lewis et al, 2005), and it has been suggested that deficits in this region could be present in the prodromal state of schizophrenia (Phillips and Seidman, 2008;Thompson et al, 2004). Moreover, the mPFC has been shown to limit the response to stress in rats and in humans (Finlay et al, 1995;Hariri et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study does not directly address cellular and molecular mechanisms of this phenomenon, one possibility is that it could result from a failure of higher cortical processes to limit the impact of stressors. The prefrontal cortex is a region that has been linked to the pathophysiology of schizophrenia (Knable and Weinberger, 1997;Lewis et al, 2005), and it has been suggested that deficits in this region could be present in the prodromal state of schizophrenia (Phillips and Seidman, 2008;Thompson et al, 2004). Moreover, the mPFC has been shown to limit the response to stress in rats and in humans (Finlay et al, 1995;Hariri et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of this group also allows differentiation between specific traits and symptoms associated with schizophrenia and their impacts on the ability in question 26,[31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…12,[15][16][17] These researches suggest that unaffected relatives of persons with schizophrenia have some similar type of phenotypes of the disorder.…”
Section: Introductionmentioning
confidence: 98%
“…10,11 Vulnerability to schizophrenia is heritable to some extent, hence, relatives specifically first-degree relatives are at higher risk of developing psychiatric disorders. 12 The chances of development of schizophrenia in siblings of affected persons are up to 10 times higher than the general population. 13 Researches demonstrated that milder forms of brain abnormalities exist in healthy relatives of persons with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%